COVID‐19 vaccine acceptability among people in Australia who inject drugs: Update from the 2021 Illicit Drug Reporting System interviews. (20th February 2022) - Price, Olivia; Dietze, Paul M.; Maher, Lisa; Crawford, Sione; Peacock, Amy
Abstract: People who inject drugs may be at higher risk of COVID‐19 transmission and more severe negative health outcomes following COVID‐19 infection. Early research on hypothetical COVID‐19 vaccines suggests this population may be less likely to accept vaccination. This commentary extends this research by presenting vaccine intention data from Illicit Drug Reporting System interviews conducted in June–July 2021, in the early stages of vaccine rollout, with people in Australia who inject drugs ( N  = 888). Half the sample (48%, n  = 419) reported that they were hesitant to receive the COVID‐19 vaccine, with key barriers relating to vaccine safety and side effect concerns. This level of hesitancy is substantially higher than that of the general population at a similar time. While we note that the subsequent Delta variant‐driven third wave of cases in Australia and efforts to increase population vaccination coverage may have altered intent in this group, this level of hesitancy warrants a targeted strategy to mitigate vaccine‐related concerns and maximise uptake. Ideally, this should comprise an inclusive health response that is peer‐led, with peer‐based organisations ideally positioned to direct immunisation service delivery and provide vaccine‐related messaging.